Effects of Vernonia amygdalina Leaf Powder on Growth Performance of Clarias gariepinus - Okukpe, K. M.; Yusuf, O. A; Adeyemo, A. D.; Omotayo, O. O.; Adeyina, A. O.; Alli, I.O.; Adeyemi-Ale, O. A; Aderibigbe, T. A; Opowoye, I. O.; Ogunsola, F. O.; Morakinyo, O. S. (Nigerian Journal of Animal Science, 2023)
Fish is a vital high quality protein necessary for growth and development. It is affected by biological and chemical substances that pollute the body of water and affects its growth during production. This often leads to the use of different antibiotic growth promoters which have residual effects on consumers of fish while sometimes continual or sub-optimal use leads to development of antibiotics resistant pathogens. This growing concern for antibiotic growth promoters in animal nutrition has elicited the need to search for phytobiotic growth promoting agents. Bitter leaf (Vernonia amygdalina) has been of use as antioxidant and growth promoter in man and some animals. The study examined the growth enhancing potential of Vernonia amygdalina leaf powder in Catfish (Clarias gariepinus) production. Two hundred and forty juvenile catfish were allotted to six treatment groups identified as A, B, C, D, E and F consisting of two replicates with twenty fishes per replicate in a Completely Randomized Design (CRD). Treatment A serve as the control, B was administered 1.5ml of known antibiotics (Florphenicol) and served as positive control while treatments C, D, E and F were administered 10, 20, 30, and 40g/15litres of water respectively for 3hours after which the water was changed. The fishes were fed 3% of their biomass twice daily 800-900 h and 1500-1600h with Durante feed containing 42% crude protein for the 8 weeks experimental period. Twenty fishes were selected per treatment and blood samples were collected by caudal vessels puncture into bijou bottles containing ethylene diamine tetracetic acid (EDTA) as anticoagulant. The result indicated that feed intake, condition factor, mean final weight, protein efficiency ratio and weight gain were significantly higher (p<0.05) in treatments B, C, D, E, F than the control (A). However, feed conversion ratio, initial weight, specific growth rate and survival percentage were not significantly different (p>0.05), though it numerically increase with the treatments. Red blood cell (RBC) and haemoglobin (Hb) concentration were significantly higher (p<0.05) than the control, while the test substance did not significantly affect other hematological parameters measured. The water quality parameters such as pH, hardness, dissolved Oxygen and Nitrate was within the recommended range and not significantly affected. Vernonia amygdalina could be used in improving fish growth and the 40g/15litres of water for 3hours was the best.